LITERATURE REVIEW OF THE INFLUENCE OF FUNDAMENTAL FACTORS ON COMPANY VALUE IN THE PLASTIC AND PACKAGING INDUSTRY SECTOR ON THE INDONESIAN STOCK EXCHANGE PERIOD 2018-2022 - Diana Prameswari (Draf Solusi Indonesia, 2023)
This research is a literature review to see theinfluence of fundamental factors on company value.The companies used in this research focus on plasticand packaging industry sector on the indonesianstock exchange companies. The research period isfrom 2018 to 2022. This research will examine 9companies using SPSS statistical tools by testingclassic assumptions and hypotheses to answer thequestions in the research.